Assessing and testing the reliability of mini self-care practices questionnaire among type 2 diabetic patients attending rural health training centre, Kanchipuram, Tamil Nadu - Selvaraj, Preethi; Boopathirajan, Ramkumar (International Journal Of Community Medicine And Public Health, 2019)
Background: India is the diabetic capital of the world with nearly 31.7 million people suffering from the disease in 2000 which is projected to become 79.4 million in the year 2030. The incidence of diabetes in India is around 8.8%. This study aims at developing a mini questionnaire to quickly assess the self-care practices among the diabetic patients attending rural health training centre and also to educate the diabetic patients about self-care practices and dietary pattern they need to follow. Methods: The study design is a community based cross-sectional study. All diabetic patients who visited rural health training centre attached to a private medical college aged 40 years and above in the period of June to July 2019 were included in our study. Institutional ethical clearance was taken before commencing the study. Construction of mini self-care practices questionnaire (MSCPQ) comprised of two phases. Trained medical students collected the data by interview method using semi-structured, pre-tested questionnaire. Results: The reliability of the MSCPQ using Cronbach’s alpha came to be 0.82 and the intra class correlation coefficient was 0.81; 95% CI (0.763-0.853) (p=<0.001). Around sixty six percent are having their health check-up regularly. Most (43%) of the study participants check their blood sugars monthly. Conclusions: Even though there are various factors contributing in facilitating self-care activities in patients living with diabetes, the role of health care physicians in educating about self-care practices are indispensable.